Extractive Spectrophotometric Determinations of Clotrimazole in Formulations - Ramachandra Rao, P.S.N.H.; Siva Rao, T.; Viplava Prasad, U.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Four simple sensitive and reproducible visible spectrophotometric methods (A–D) for the determination of clotrimazole (CTZ) in bulk samples and pharmaceutical formulations are described. Methods A, B and C are based on the formation of ion-association complexes between CTZ and tropaeolen-000 (Tp000, λmax 480 nm), supracen violet 3B (SV3B, λmax 560 nm) or wool fast blue BL (WFB, λmax 580 nm). Method D is based on the formation of a molecular complex between CTZ and cobalt thiocyanate (CTC, λmax 600 nm). Regression analysis of Beer's plots showed good concentration ranges: 1.0–6.0 μg/mL for methods A, B and C and 1.25-7.5 μg/mL for method D. No interference was observed from the usually existing additives in pharmaceutical formulations and the applicability of the methods was examined by analysing cream and powder containing CTZ. Relative standard deviations were typically ≤ 0.33%. Recoveries were ≥ 99.5%.